2006
DOI: 10.1037/0278-7393.32.5.983
|View full text |Cite
|
Sign up to set email alerts
|

On the psychology of the recognition heuristic: Retrieval primacy as a key determinant of its use.

Abstract: The recognition heuristic is a prime example of a boundedly rational mind tool that rests on an evolved capacity, recognition, and exploits environmental structures. When originally proposed, it was conjectured that no other probabilistic cue reverses the recognition-based inference (D. G. Goldstein & G. Gigerenzer, 2002). More recent studies challenged this view and gave rise to the argument that recognition enters inferences just like any other probabilistic cue. By linking research on the heuristic with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 71 publications
5
94
3
Order By: Relevance
“…As most previous investigations of this choice context have not included measures of subjective magnitude (but see Pachur & Hertwig, 2006), we cannot evaluate MaC directly. However, by addressing these additional findings, we hope to illustrate the explanatory power of MaC and, at the same time, lay out a set of predictions that might serve as the basis for future research.…”
Section: Mac Account Of Other Findings In the Rh Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…As most previous investigations of this choice context have not included measures of subjective magnitude (but see Pachur & Hertwig, 2006), we cannot evaluate MaC directly. However, by addressing these additional findings, we hope to illustrate the explanatory power of MaC and, at the same time, lay out a set of predictions that might serve as the basis for future research.…”
Section: Mac Account Of Other Findings In the Rh Literaturementioning
confidence: 99%
“…We postpone the review of other RT-related findings to the General Discussion, where we show how they relate to and are compatible with the MaC framework. Pachur and Hertwig (2006;see also Volz et al, 2006) found that comparative judgments involving RU pairs are, on average, faster when the recognized pair member is chosen than when the unrecognized pair member is chosen. The authors attribute this finding to the "retrieval primacy" of recognition.…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations